Bridging Istinbāṭī and Taṭbīqī: An Integrative Ijtihād Model for Halal Fatwa Governance and Regulatory Compliance - Holis Holis; Umi Indasyah Zahro; Lailatul Maghfiroh; Hawa Gazani; Imamuddin; Wasif Naif Nahar Daqamseh (Nusantara: Journal of Law Studies, 2026)
This study investigates the integration of ijtihād istinbāṭī and ijtihād taṭbīqī in the formulation of halal fatwas for processed food products in Madura, Indonesia. The research addresses persistent reliance on fragmented fatwa methodologies, which have historically engendered legal ambiguity, interpretive divergence, and challenges to the legitimacy of religious authority. Employing a qualitative descriptive methodology, the study combines doctrinal analysis with field observations and in-depth interviews involving ulama, food industry stakeholders, and representatives of halal certification bodies. Findings demonstrate that halal fatwa determination in Madura is contingent upon the synergistic application of istinbāṭī ijtihād, which provides normative and doctrinal legitimacy, and taṭbīqī ijtihād, which facilitates the contextualization of Islamic legal norms within contemporary socio-technological and industrial frameworks. This unification produces an integrative ijtihād model in which Islamic law is dynamically aligned with empirical realities and public welfare considerations (maqāṣid al-sharī‘ah). Operationalization occurs through collaborative governance mechanisms involving regional MUI branches, Halal Inspection Agencies (LPH), pesantren networks, and academic institutions, yielding halal fatwas that are simultaneously legally authoritative and socially responsive. The study further suggests that adopting a unified ijtihād framework can enhance the coherence, legitimacy, and legal certainty of halal fatwa production, while concurrently strengthening national halal governance by harmonizing religious authority, regulatory institutions, and industrial practices. The findings contribute to contemporary Islamic legal scholarship by demonstrating how integrative jurisprudential methodologies can reconcile classical Sharīʿah principles with modern technological, socio-economic, and policy imperatives.